SPH modelling of multi-fluid lock-exchange over and within porous media. (October 2017) - Basser, Hossein; Rudman, Murray; Daly, Edoardo
Highlights: Explicit Incompressible SPH (EISPH) was applied to multi-fluid flow in porous media. EISPH reproduced experiments of fluids flowing between media with different porosity. EISPH was able to simulate multi-fluid flows across a range of density differences. The model reproduced detail dynamics at the interface between different fluids. Abstract: Multi-fluid flow over and within porous media occurs frequently in nature and plays an important role in engineering applications. The modeling of these flows and validation against experimental or field observations have not been largely conducted in literature. An explicit numerical scheme for incompressible fluid using Smoothed Particle Hydrodynamics (EISPH) was employed and solved using two integration algorithms. To explore the capabilities and limitations of the model, case studies including percolation of a single fluid in a porous medium, gravity current of a single fluid over a porous medium, multi-fluid flow over an impermeable bed, and a porous medium were simulated and compared with experimental data. The EISPH method led to results overall similar to the observed experimental data. The model was able to reproduce the behaviour of the flow within media with different porosities. In addition, the model reproduced behaviour of multi-fluid flow at the interface between different fluids, such as reproducing Kelvin–Helmholtz vortices and diffusion of salt.